Analisis Potensi Ekowisata Berbasis Masyarakat di Desa Burai Sumatera Selatan - Detmuliati, Alditia (Samarinda State Polytechnic, 2021)
In 2021 the Province of South Sumatra brought home 8 awards at the Anugrah Pesona Indonesia. It awarded one of the second place in the Burai Village award in the category of Most Popular Ecotourism Village in Indonesia. I conducted this research to explore the potential of ecotourism in Burai Village. This study uses a community-based research (CBR) approach which is implemented with a Participatory Action Research (PAR) approach. Some potentials found include building floating / non-permanent buildings on the river, make Lima's house and Bari house a homestay. , Pindang and Kemplang are special foods that tourists can enjoy., Song key and Purun are souvenirs from Burai Village, bummer dance as performance in Burai Village, offers several activities on community agricultural land without having to change the contents of the agricultural land.